Human Breast Cancer Cells Demonstrate Electrical Excitability - Ribeiro, Mafalda; Elghajiji, Aya; Fraser, Scott P.; Burke, Zoë D.; Tosh, David; Djamgoz, Mustafa B. A.; Rocha, Paulo R. F. (Frontiers in Neuroscience, 2020)
Breast cancer is one of the most prevalent types of cancers worldwide and yet, its pathophysiology is poorly understood. Single-cell electrophysiological studies have provided evidence that membrane depolarisation is implicated in the proliferation and metastasis of breast cancer. However, metastatic breast cancer cells are highly dynamic microscopic systems with complexities beyond a single-cell level. There is an urgent need for electrophysiological studies and technologies capable of decoding the intercellular signalling pathways and networks that control proliferation and metastasis, particularly at a population level. Hence, we present for the first time non-invasive in vitro electrical recordings of strongly metastatic MDA-MB-231 and weakly/non-metastatic MCF-7 breast cancer cell lines. To accomplish this, we fabricated an ultra-low noise sensor that exploits large-area electrodes, of 2 mm2, which maximizes the double-layer capacitance and concomitant detection sensitivity. We show that the current recorded after adherence of the cells is dominated by the opening of voltage-gated sodium channels (VGSCs), confirmed by application of the highly specific inhibitor, tetrodotoxin (TTX). The electrical activity of MDA-MB-231 cells surpasses that of the MCF-7 cells, suggesting a link between the cells’ bioelectricity and invasiveness. We also recorded an activity pattern with characteristics similar to that of Random Telegraph Signal (RTS) noise. RTS patterns were less frequent than the asynchronous VGSC signals. The RTS noise power spectral density showed a Lorentzian shape, which revealed the presence of a low- frequency signal across MDA-MB-231 cell populations with propagation speeds of the same order as those reported for intercellular Ca2+ waves. Our recording platform paves the way for real- time investigations of the bioelectricity of cancer cells, their ionic/pharmacological properties and relation to metastatic potential.